2019
DOI: 10.21031/epod.564819
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Student and School Level Characteristics on Academic Achievement of Middle School Students in Turkey

Abstract: The purpose of the study was to examine the student-level and school-level variability that affect middle school students' academic achievement. Student background and school context on student academic achievement were examined. Participants of the study consisted of 1053 seventh and eighth grade middle school students from 10 schools in the cities of Ankara and Sinop, Turkey. The research study analysed using two-level hierarchical linear modeling (HLM). Data were analysed with three HLM models: (1) random e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Inequalities among students can exist in many aspects, such as class, race, gender, sexual orientation, disability status, family economic status, parental education level, age at school entry, and immigration background (Aslanargun et al, 2016;Close & Shiel, 2009;Gürsakal, 2012;Karaman & Atar, 2019;Schneider, 2018;Yetişir & Batı, 2021). In addition, it has been observed that variables such as mathematics self-e cacy, anxiety, and attitude toward mathematics have signi cant effects on mathematics achievement (Ayebale et al, 2020;Kalaycioglu, 2015;Ötken, 2021).…”
Section: School and Student Level Variables In Large Scale Assessmentsmentioning
confidence: 99%
“…Inequalities among students can exist in many aspects, such as class, race, gender, sexual orientation, disability status, family economic status, parental education level, age at school entry, and immigration background (Aslanargun et al, 2016;Close & Shiel, 2009;Gürsakal, 2012;Karaman & Atar, 2019;Schneider, 2018;Yetişir & Batı, 2021). In addition, it has been observed that variables such as mathematics self-e cacy, anxiety, and attitude toward mathematics have signi cant effects on mathematics achievement (Ayebale et al, 2020;Kalaycioglu, 2015;Ötken, 2021).…”
Section: School and Student Level Variables In Large Scale Assessmentsmentioning
confidence: 99%